(untitled) (World Economics and Finance Bulletin, 2026)
In the context of global economic transformation, SMEs are a key driver of sustainable growth, employment, and innovation. This study outlines the theoretical foundations of the financial support mechanism and identifies its priority areas for improvement. Focusing on Uzbekistan, it highlights the need to expand financial access and strengthen institutional frameworks